Analysis of selling price setting mechanisms and services in the perspective of Islamic economics (Case study of photocopying and printing Ammey Kel. Dermayu Kab. Seluma Prov. Bengkulu) - Siti Muslihatun (Digital Business: Tren Bisnis Masa Depan, 2022)
The purpose of this study was to find out how the mechanism for setting selling prices and services for Photocopying and Printing Ammey Kel. Dermayu Kab. Selum Prov. Bengkulu and to find out how the Islamic economic review of the mechanism for setting selling prices and services on Ammey's Photocopying and Printing. To reveal this issue in depth and comprehensively, the authors used qualitative methods to collect the information needed during the research period. The data collection for this research was carried out by conducting observations or observations and interviews, with research objects at Ammey Photocopying and Printing. using fairness-based pricing, the pricing at Ammey Photocopying and Printing is in accordance with Islamic economic principles because the prices set do not tyrannize the buyer, namely Ammey Photocopying and Printing take advantage of the interest rate horse. Photocopying and Printing Ammey does not take advantage of the round off price, but the rest of the round off will be collected and diverted to social funds and to the mosque's charity box. and the determination of price rounding is a balance point between the forces of supply and demand which are agreed voluntarily and voluntarily by sellers and buyers.